Effect of bioactive compounds in evaluation of hepatoprotective efficacy of the hydro alcoholic crude extract of Sphaeranthus amaranthoides (Asteraceae) leaf against CCl4-Induced hepatotoxicity in Wistar rats - Anima JENA; Nityananda SAHOO; Prasanth DAMARSINGU (Notulae Scientia Biologicae)
The hydroalcoholic extract of Sphaeranthus amaranthoides (Asteraceae) entire part was screened for hepatoprotective activity on carbon tetrachloride-induced hepatotoxic in Wistar rats. Plant extract was screened for phytochemicals and GC MS study was also carried out for identification of compounds. Further, hepatoprotective activity was performed where carbon tetrachloride and corn oil mixture (1:1 v/v) was injected at 2 ml/kg body weight on the 6th day. The rats were treated with hydroalcoholic extract of SA at the doses of 250 mg/kg and 500 mg /kg body weight daily for 14 days, orally. Results were compared with standard silymarin (10 mg/kg b.w). After completion of observation duration (up to 21 day), all rats were sacrificed and blood was collected. The level of biomarkers of liver injury viz. serum glutamate pyruvate transaminase (SGPT), oxaloacetate transaminase (SGOT), alkaline phosphate (ALKP), total protein (TP), total bilirubin was analysed. Further, change in body weight, liver weight, and histopathologic examination were conducted. Finally, the result concluded that SA extract is an useful therapeutic herb to prevent hepatic impairment due to the presence of various terpenoids, acid esters, phenolics, phytosterols etc. as major groups of compounds identified by GCMS in the plant.